From spermatocytes to sperm: meiotic behaviour of human male reciprocal translocations - Oliver-Bonet, M.; Navarro, J.; Codina-Pascual, M.; Abad, C.; Guitart, M.; Egozcue, J.; Benet, J. (Human reproduction (Oxford), 2004)
BACKGROUND: Human male translocation carriers may present alterations in the meiotic process due to the presence of the translocated chromosomes. The aim of this work was to study the mechanisms that affect meiotic segregation in translocation carriers by analysing different stages of the meiotic process. METHODS: Meiotic studies using fluorescence in-situ hybridization on both spermatocytes and sperm nuclei were performed in two translocation carriers, t(11;17)(q13.1;p11.2) and t(10;14)(q24;q32). RESULTS: A ring configuration was the main type of quadrivalent found in metaphase I. Overall chiasma frequency was significantly decreased in the t(11;17) carrier. In the t(10;14) carrier, chiasma frequency within the interstitial region of chromosomes 10 and 14 was increased and the recombination pattern was modified. As expected from the frequencies of interstitial chiasmata found in metaphase I in the two subjects, the incidence of asymmetric dyads was sporadic in t(11;17) and very high in t(10;14). In both carriers, segregation frequencies observed at metaphase II were not different from the segregation data obtained in decondensed sperm nuclei. CONCLUSIONS: The concordance observed among results obtained in different spermatogenic stages indicates an absence of cellular selection based on chromosomal imbalances. Results obtained in the aneuploidy assay have not provided any evidence for an interchromosomal effect.